SMEs AND INNOVATION – CASE OF MACEDONIA - ANETA RISTESKA JANKULOSKA; KOSTA SOTIROSKI; MIROSLAV GVEROSKI; Tatjana Spaseska; FANKA RISTESKA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
Considering the dynamic environment, competitiveness of small and medium enterprises depends on the speed with which new products can be presented in the market. Innovation represent specific instrument of entrepreneurship, and in general entrepreneurs are bringing innovation. Innovation represents activity that impregnates the existing resources with new capacities for creation of resources. Innovation sometimes may result in brand new, unknown product or replacement of some existing function for it’s more efficient and successful performance. SMEs are more innovative than larger firms, due to their flexibility and their ability to quickly and efficiently integrate inventions created by the firms’ development activities. Hence, in this paper the main focus will be on SMEs in Macedonia, their innovation and the business environment, excually the influence of business environment for creating innovation. To prove this we will test three hypotheses by using the ANNOVA model and in the end of the paper based on the obtained results we will purpose a measures for improving the business environment in Macedonia in order to stimulate SMEs innovation.